Detection of soybean rust caused by Phakopsora pachyrhizi in northwestern Argentina. - Ploper, Leonardo Daniel (2005)
Asian soybean rust, caused by Phakopsora pachyrhizi, is regarded as one of the most destructive diseases of soybean [Glycine max (L.) Merr.]. In Argentina, it was first detected in the province of Misiones in northeastern Argentina near Paraguay and Brazil during the 2001-02 growing season.  The following season it also was found in the neighboring province of Corrientes.  However, it did not reach major soybean production areas in northern Argentina until the end of the 2003-04 season.  In April 2004, as soybean crops were nearing maturity, the disease was found throughout the region of northwestern Argentina, which includes the provinces of Tucumán, Salta, Jujuy, Catamarca, and Santiago del Estero, where approximately 6% of the soybean crop of Argentina is produced.  During February and March the area had a severe drought and above average temperatures, but in April rainfall was abundant, particularly during the first half of the month.  Soybean rust was first observed on 16 April in several locations of the departments (counties) of Moreno and Jimenez in the province of Santiago del Estero, and the following week in the departments of Alberdi, Burruyacu, Cruz Alta, Famaillá, La Cocha, and Leales in the province of Tucumán; in the department of Santa Rosa in the province of Catamarca; and in the departments of Anta, Metán, Rosario de la Frontera, and San Martín in the province of Salta.  In those fields where the disease was detected, nearly all plants showed symptoms.  Affected crops were mostly in growth stages R7 to R8, except for a few fields that had been planted late and were in a late R5 stage.  Yield losses of up to 28% and premature defoliation occurred in these fields only.  Disease severity, measured as percentage affected leaf area, ranged from 45 to 50% in untreated fields and from 0.9 to 39% in fungicide-treated fields. Leaf lesions were reddish-brown, irregularly shaped, and were more abundant on the abaxial surface.  Under the dissecting microscope, uredinia were observed as erumpent pustules with a conspicuous central pore.  Masses of urediniospores were expelled through the pore and covered the pustules. Urediniospores were hyaline to pale yellow-brown, sub globose to ovoid, with finely echinulate, hyaline walls and an average size of 27.8 x 18.5 ¦Ì.  Because there are two morphologically similar species of Phakopsora that infect soybean, P. pachyrhizi (the Asian species) and P. meibomiae (the New World species), a molecular differentiation was carried out using the PCR assay described by Frederick et al.  DNA extracted from 37 samples from different locations was amplified using specific primers for both species of Phakopsora and specific primers for P. pachyrhizi and for P. meibomiae.  Twenty-eight samples amplified with the two-species primers and with the P. pachyrhizi primer.  None of the samples amplified with the P. meibomiae primer.  Specimens have been deposited at Instituto Miguel Lillo, Tucumán, Argentina.  These results confirmed the presence of P. pachyrhizi in the provinces of Catamarca, Tucumán, Salta, and Santiago del Estero, Argentina